Issue Notes - , Editor (Historical Papers, 2022)
The following papers were presented to the Canadian Society of Church History in 2011, but were not made available for publication: Bruce Douville, “Back to the Garden (Again): Re-examining the Jesus People Movement in Toronto”; Russell Prime, “The Church and the Magistrate: Glimpses of Church-State Relations in a New Brunswick Coastal Community, 1880-1930”; Robert Dennis, “The Douglas Chair in Canadian and Colonial History: Philanthropy, Secularization, and Restructuring Queen’s University in the Early Twentieth Century”; Mark A. Noll, “The History of the Bible in Canada and the United States”; Marguerite Van Die, “‘Beyond the Protestant Nation’: U.S. Historiographical Debate and Canadian Narratives of Religion and Society”; Joel Kropf, “The Practicality of the Common Good: Catholic Moral Reasoning, the Postwar Instrumentalist Mentality, and the Canadian Death-Penalty Debate”; Margie Patrick, “The Nature of Canada’s Religious Right: The Evangelical Fellowship of Canada and Evangelical Political Engagement”; Ji-il Tark, “Canadian Missions for Koreans in North-East Asia, 1898- 1942”; Gordon Heath, “Canadian Churches and War: An Introductory Essay and Annotated Bibliography”; and Stephen Dutcher, “Eastern Co-op Services and the Post-World War Two Legacy of the Antigonish Movement.”